The Effect of Using Shadowing Technique Towards Students’ Speaking Skill at The Eleventh Grade Student of SMAN 10 Pandeglang in Academic Year 2021/2022 - Adromi, Adromi; Gumelar, Rizdki Elang; Munawaroh, Tatu (Universitas Mathla'ul Anwar Banten, 2023)
The purpose of the research is to know whether the use of shadowing technique gives significant effect towards students speaking skill at the eleventh-grade students of SMAN 10 Pandeglang. The research approach used is quantitative approach, while the method used is quasi experimental with pre-test and post-test control group design. The population of this research consists of 90 students and the sample of this research consists of 60 students. The data was analyzed by using statistical of program SPSS 22. Based on result of the data analysis, the finding shows that there is significant effect of using shadowing technique towards student’s speaking skill at the eleventh-grade students of SMAN 10 Pandeglang. It can be seen from the results of t-test obtained sig value 0.000<=α 0.05. It can be concluded that there is significant effect of using shadowing technique towards students’ speaking skill at the eleventh-grade students of SMAN 10 Pandeglang.